Competency of Seniors with Dementia to Live Independently and Manage Finance: Synthesis of the Legislation in Quebec - Giroux, Dominique; Robichaud, Line; Tétreault, Sylvie; Langlois, Lyse (Canadian Review of Social Policy / Revue canadienne de politique sociale, 2013)
The socio demographic data report that the population will double in less than 30 years in Quebec (Curateur public du Québec, 2010a). This situation is concerning due to increasing health problems associated with aging. The socio demographic reality brings an additional challenge for health and social professionals who have a key role in regard to the assessment of the ability of seniors to live independently and manage finances. The aim of this article is to summarize the Quebec’s legislation related to the competency assessment. The competency assessment is a complex process, which implies the consideration of various components: legal, ethical and clinical. No assessment tool is available in Quebec to support the health care professionals in the assessment process of competency of a person to live independently and manage finances. Considering these increasing problems, it appears imperative to consider the assessment process of competency to provide to the Quebec’s health care professionals valid assessment tools for an objective and rigorous assessment.